Html 3.2 and cgi unleashed : professional reference edition - December, John.; Ginsburg, Mark. ([S.l.] : Sams Publishing, 1996)
A detailed reference for experienced Web developers who need to provide information on the Web and on Intranets, and produce Web pages. The text covers the development, planning, analysis, design, implementation, promotion and maintenance of a site.